The Effect of Compensation and Work Stress on Employee Performance at the Cahaya Putra Selatan Group Rehabilitation Institute - Muhammad Fabil Al Baar; Afriyadi Cahyadi; Reska Rahmatullah (Universitas Muhammadiyah Palu, 2026)
Social rehabilitation institutions are a process of refunctionalization and development to enable individuals to carry out their social functions appropriately in society. Social rehabilitation is an alternative for the recovery of drug addicts. For the rehabilitation process to run smoothly, high-performing employees are essential. The purpose of this study was to determine the effect of compensation and job stress on employee performance at the Cahaya Putra Selatan Group rehabilitation institution. Data collection was conducted by distributing questionnaires to 85 employees of the Cahaya Putra Selatan Group Rehabilitation Institution. The results of this study indicate that compensation has a positive and significant effect, while job stress has a negative and significant effect on employee performance at the Cahaya Putra Selatan Group rehabilitation institution.